Notes on the Origin of Greek Tyrannis - Hegyi, Dolores
The institution and name of Tyrannis was of Lydian origin; several of the Greek political terms came from the Lydian language; *turanna-, Phrygian *turannas, Luwian *turawanaš (Suffix -wanaš); the first part of the word tyrannos is problematical (*ldanś < *lda- “to rule?, cf. p. 314 ff.; Vgl. die ungar. Fassung in AnTan 12 (1965) .191-203.